Effect of capsaicin and cimetidine on the healing of acetic acid induced gastric ulceration in the rat. Issue 6 (June 1996) - Kang, J Y; Teng, C H; Chen, F C
Abstract : BACKGROUND: Capsaicin protects the gastric mucosa against experimental injury while capsaicin desensitisation reduces the rate of gastric ulcer healing. The effect of exogenous capsaicin on gastric ulcer healing has not to date been reported. AIM/METHOD: To investigate the effect of capsaicin, cimetidine, and in combination, given intragastrically in the healing of acetic acid induced chronic gastric ulcer in the rat. Treatment started immediately after ulcer induction. RESULTS: At the end of one week, capsaicin, cimetidine, and in combination increased ulcer healing but the effect of combined treatment was less than that of capsaicin alone. In an in vivo gastric chamber preparation, capsaicin increased, while cimetidine decreased, gastric mucosal blood flow measured by laser Doppler flowmetry. A dose response effect in reduction of gastric mucosal blood flow could be demonstrated for cimetidine. The gastric hyperaemic effect of capsaicin was blunted by prior administration of cimetidine. In contrast, capsaicin had no effect on gastric acid secretion and its addition to cimetidine did not affect the acid suppressant effect of the latter. CONCLUSIONS: Capsaicin promotes the healing of acetic acid induced gastric ulcer, probably by its gastric hyperaemic effect. Although cimetidine also promotes ulcer healing due to its inhibitory effect on acid secretion it may have an antagonistic effect on the gastric ulcer healing effect of capsaicin by virtue of inhibition of gastric hyperaemia.